Analysis of The Utilization of Posbindu Program Services For Non-Communicable Diseases (NCDS) In The Community at the M Public Health Center - Sirait, Reni Aprinawaty; Riady Suranta Sinuhaji (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Non-communicable diseases have become the main cause of death globally and nationally, due to the high number of NCDs which continue to increase every year, so to control PTM risk factors in Indonesia, the government established the Posbindu PTM program. However, the utilization of Posbindu PTM in the working area of the Brand Health Center has not reached the target of 100%. This study aims to determine the factors associated with the utilization of Posbindu PTM. This type of research is quantitative with cross-sectional design and the analysis used is univariate and bivariate. The population in this study were people suffering from non-communicable diseases in the working area of the Brand Health Center. The sample in this study amounted to 100 people. The results showed that out of 100 respondents, 60.0% used Posbindu PTM. Variables related to the utilization of Posbindu PTM were knowledge (p=0.001), mileage (p=0.011), family support (p=0.004), attitude (p=0.001), and health status (p=0.002). The variable that is not related to the utilization of Posbindu PTM is the variable support from health workers (p=0.423). It is recommended for puskesmas to further improve the quality of life of the community through collaboration with health workers such as cadres..